2021
DOI: 10.3390/en14206829
|View full text |Cite
|
Sign up to set email alerts
|

Households’ Electrical Energy Conservation and Management: An Ecological Break-Through, or the Same Old Consumption-Growth Path?

Abstract: We examine the motivations behind the electrical energy conservation and smart management at households to verify whether we are observing an ecological breakthrough, or a mere continuation of the well-trodden consumption-growth path. We conducted an online survey in France, Spain, Italy, and Denmark (n = 3200) on the subject of electricity use and generation. We utilized a generalized structural equation model to simultaneously test the direct reasons behind different energy-use behaviors and intentions, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 74 publications
1
8
0
Order By: Relevance
“…In addition, other scholars discuss how social comparison, competition among peers, and goal setting for energy conservation can become more effective means to mobilize the potential for households' energy transition at home [75][76][77][78][79]. Contrasting opinions emerge also on this point: while Schneider et al illustrate the role of individual energy coaches for this purpose [80], Jorgensen et al argue that group-targeted interventions are more successful than individualistic approaches [81].…”
Section: How To Mobilize the Adoption Of Energy Conservation Practicesmentioning
confidence: 99%
“…In addition, other scholars discuss how social comparison, competition among peers, and goal setting for energy conservation can become more effective means to mobilize the potential for households' energy transition at home [75][76][77][78][79]. Contrasting opinions emerge also on this point: while Schneider et al illustrate the role of individual energy coaches for this purpose [80], Jorgensen et al argue that group-targeted interventions are more successful than individualistic approaches [81].…”
Section: How To Mobilize the Adoption Of Energy Conservation Practicesmentioning
confidence: 99%
“…Many studies have indicated that promoting energy saving can significantly reduce the amount of energy wasted (e.g., [11][12][13][14][15][16][17]). This is important in the context of pursuing the ambitious strategies and goals set out in the Kyoto Protocol (1997), the Paris Agreement (2015), and, most recently, at the COP26 Climate Summit in Glasgow (2021), which, in turn, reduces the risk of dangerous effects of climate destabilization [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have confirmed that changing human behavior has a large impact on energy saving and environmental sustainability (e.g., [19,[28][29][30][31][32][33][34][35][36]). However, they explained that various obstacles increase energy efficiency [37] and proved that traditional media campaigns that promote pro-ecological knowledge and attitudes through simple dissemination of information often do not bring a lasting change in behavior [23,38,39].…”
Section: Introductionmentioning
confidence: 99%
“…The United Nations Framework Convention on Climate Change (COP26) remarks that there must be a commitment to systemic change and net zero emissions should be a part of business principles and operation [15]. Despite a high level of consumption of energy by business, studies on energy conservation have tended to focus on individuals at home [16,17]. However, the results of the studies that focus on household energy conservation at home may not be generalised to the business context [18].…”
Section: Introductionmentioning
confidence: 99%